Mathematical modelling of hydraulics and water quality characteristics for small dam maintenance - Prastica, Rian Mantasa Salve; Soeryantono, Herr; Marthanty, Dwinanti Rika (Peter the Great St. Petersburg Polytechnic University, 2022)
Along the inclining events of flooding events, maintenance towards water infrastructure such as urban small dam is needed. The maintenance needs interdisciplinary approach involving hydrology, hydraulics, water quality, and sediment factors. Due to lack of studies in those fields, the study aims to construct a model by using RESOURCE MODELLING ASSOCIATES program to study behaviours of hydraulics and water quality as small dam management. Numerical modelling, hydrology analysis, hydraulics assessment, water quality tests, and field works are employed in this study, with Agathis small dam as a case. The model could run successfully which the result concludes that the model produces reasonable result with acceptable errors and value of R2. A scenario of constructed wetland is proposed and has good accuracy for future maintenance for hydrology, hydraulics, and environmental management. In addition, the models also could be applied to other problem such as an agricultural field also. In the near future, studies about hydrodynamics and water quality modelling especially sediment on small dams need to be more explored because few studies still have limited information meanwhile they have essential impact towards urban water management. © 2022 St-Petersburg State Polytechnical University. All rights reserved.